Deskriptif Analitik Penyaluran Bantuan Sosial Program Keluarga Harapan (PKH) Desa Manggis, Kecamatan Mojosongo, Kabupaten Boyolali. - Ayu Nanda, Farischa Martya; Pramono, Joko; Kusuma W, Purbayakti (Solidaritas, 2024)
The problem of distributing PKH social assistance in Manggis Village, Mojosongo District, Boyolali Regency is a serious problem. Program Keluarga Harapan aims to open KPM access for pregnant women and toddlers to utilize health facilities and educational facilities. The inaccuracy of targeting social assistance recipients is a problem that arises when social assistance is disbursed by the government, those who are supposed to get it do not get it and vice versa, they should not be entitled to it, but instead get it. This research aims to analyze and describe descriptive analytics of PKH social assistance distribution. The method used is qualitative research to describe descriptive analytics of PKH social assistance distribution by referring to the principal agent theory proposed by Eisenhardt (1988). There are 5 indicators proposed, namely the delegation of authority, the existence of parties working together, the existence of planning, the dominance of one party over another, and the existence of different interests in the PKH social assistance program. Data was collected through observation, interviews, literature and document studies, then analyzed using the stages of collection, reduction, presentation and drawing conclusions. The research results show that the principal agent indicators in PKH social assistance display various patterns. The delegation of authority is quite good, the parties working together are quite good, the planning in general is still lacking, the dominance of one party over another is somewhat lacking, and the existence of different interests is also somewhat lacking. Setting the mechanism for accepting PKH recipients consists of 2 mechanisms, namely setting the criteria for PKH recipients and setting the process for determining PKH recipients. The factors causing the implementation of PKH social assistance to be not optimal in Manggis Village are due to the DTKS not being updated regularly, as well as the problem of the principal agent, namely closeness to the village head/village officials and the RT head. Keywords : Program Keluarga Harapan, Principal Agent.